PENERAPAN TEKNOLOGI EKSTRAKSI FASA CAIR-GAS PADA PENGEMBANGAN PRODUK BERBASIS JERUK KALAMANSI - Evi Maryanti; Dyah Fitriani; Nori Wirahmi (DHARMA RAFLESIA, 2018)
Community Service Activity (CSA) of the application of science and technology entitled "Application of Liquid-Gas Phase Extraction Technology on Development of Kalamansi-Orange-Based Products" has been completed. This activity aims to implement gas-liquid extraction technology, namely steam distillation in extracting essential oils from residues of Kalamansi orange syrup processing, providing knowledge and ways to process Kalamansi orange essential oil into products which have economic value in addition to syrup. It was carried out with the target audience, namely Bhakti Nusa Production Unit in SMKS 16 Bengkulu. It is done to help the production unit to develop Kalamansi-based products by utilizing residues produced by syrup which is rich in essential oils. The products produced on the CSA of the application of science and technology include aromatherapy candles, air freshener gels, anti-mosquito lotions and Bay Tat cakes of Kalamansi jam. The product produced is more widely informed through the socialization activity that received a response and enthusiasm from the audience. Products of CSA of the application of science and technology are expected to be a superior product from the Bhakti Nusa Production Unit of SMKS 16 Pharmacy as well as to be a top-quality product of the pride of Bengkulu City with high economic value. Keywords: Extraction, Liqiud-Gas, Kalamansi, Essential oil